Risk factors for antibiotic resistance development in healthcare settings in China: a systematic review - Chen, Qi; Li, Duguang; Beiersmann, Claudia; Neuhann, Florian; Moazen, Babak; Lu, Guangyu; Müller, Olaf (Epidemiology and infection, 2021)
Antibiotic resistance (ABR) threatens the effectiveness of infectious disease treatments and contributes to increasing global morbidity and mortality. In this study, we systematically reviewed the identified risk factors for ABR among people in the healthcare system of mainland China. Five databases were systematically searched to identify relevant articles published in either English and Chinese between 1 January 2003 and 30 June 2019. A total of 176 facility-based references were reviewed for this study, ranging across 31 provinces in mainland China and reporting information from over 50 000 patients. Four major ABR risk factor domains were identified: (1) sociodemographic factors (includes migrant status, low income and urban residence), (2) patient clinical information (includes disease status and certain laboratory results), (3) admission to healthcare settings (includes length of hospitalisation and performance of invasive procedures) and (4) drug exposure (includes current or prior antibiotic therapy). ABR constitutes an ongoing major public health challenge in China. The healthcare sector-associated risk factors was the most important aspect identified in this review and need to be addressed. Primary health care system and ABR surveillance networks need to be further strengthened to prevent and control the communicable diseases, over-prescription and overuse of antibiotics.
Published online: 03 June 2021
Gesehen am 23.12.2021